Arene CH=O hydrogen bonding : a stereocontrolling tool in palladium-catalyzed arylation and vinylation of ketones - Huang, Zhiyan (2013)
Weak is powerful: For the arylation of tin enolates, the palladium catalyst engages in weak CH=O hydrogen bonds to control stereoselectivity (see scheme). Similar catalysts capable of NH=O hydrogen bonding also works well.